Phytochemical, Antimicrobial and Cytotoxic Activities of Strophanthus sarmentosus DC - Julius Leke Abiola; Olapeju Oluyemisi Aiyelaagbe (Biology, Medicine, & Natural Product Chemistry, 2023)
Strophanthus sarmentosus DC is used traditionally in the management of snake-bite, arthritis, eye infection, rheumatism, emetic and venereal diseases. Freshly collected mature Strophanthus sarmentosus plant parts were air-dried at room temperature. Each of the plant parts (leaf, stem and roots) was successively extracted by cold extraction method using hexane, ethyl acetate and methanol respectively. The crude extracts were subjected to phytochemical, antimicrobial and cytotoxicity analysis by employing chemical tests, agar diffusion and brine shrimps methods.The phytochemical screening showed the presence of tannins, saponins, glycosides, flavonoids, phenols, steroids, terpenoids and carbohydrates in all the extracts. The extracts demonstrated broad spectrum activities against both gram- positive and gram-negative bacteria and the fungi tested. The MIC and MMC of ethyl acetate and methanol extracts of the S. sarmentosus (stem) is between 0.3 and 5.0 mg/mL. The cytotoxic activity (LC50) of the S. sarmentosus extracts (leaf, stem and root) ranged between 117 g/mL and 270 g/mL, showing that the extracts are within the medium toxic level according to Clarksons toxicity index.